2020
DOI: 10.1002/hup.2763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aripiprazole long‐acting injectable antipsychotic on hospitalization in recent‐onset schizophrenia

Abstract: Objective: Recent-onset schizophrenia (ROS) represents a critical period that can greatly influence the clinical course of schizophrenia. The use of long-acting injectable antipsychotics (LAIs) in this period is increasingly being considered as a first-line treatment option. Aripiprazole LAI (ALAI) is the newest of all LAI's available on the market, with limited data on its effects on hospitalization rates after first episode of schizophrenia. It was our goal to evaluate whether ALAI has an effect on hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Published data on the real-life effectiveness of aripiprazole LAI have only recently been published [ 36 ]. Three small mirror-image studies have reported findings for aripiprazole LAI that are in agreement with our findings [ 8 , 37 , 38 ]. For example, one study evaluated 148 UK patients (65% with schizophrenia) receiving aripiprazole LAI between 2014 and 2018 and reported >79% reductions in hospitalization number and duration in both fully compliant and partially compliant (≥50% of injections) patients in the 2-year period following LAI initiation [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Published data on the real-life effectiveness of aripiprazole LAI have only recently been published [ 36 ]. Three small mirror-image studies have reported findings for aripiprazole LAI that are in agreement with our findings [ 8 , 37 , 38 ]. For example, one study evaluated 148 UK patients (65% with schizophrenia) receiving aripiprazole LAI between 2014 and 2018 and reported >79% reductions in hospitalization number and duration in both fully compliant and partially compliant (≥50% of injections) patients in the 2-year period following LAI initiation [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Currently, SGA LAIs are infrequently used as first-line therapy. However, Karlovic et al 13 suggest they should be considered for patients with recent-onset schizophrenia (ROS), 14 reporting reduced use of hospital services at 1-year follow-up of ROS patients prescribed aripiprazole.…”
Section: Secondary Observationsmentioning
confidence: 99%
“…9,10 Several studies have shown that aripiprazole once monthly 400 mg (AOM400) effectively reduced hospitalization time and improved patient functionality. [11][12][13] Its safety profile was assessed in clinical trials that showed good tolerability and a low incidence of AEs. 14 The initial single-injection start regimen consists of a single intramuscular injection with concomitant oral aripiprazole administration for 14 consecutive days to maintain therapeutic drug concentrations.…”
mentioning
confidence: 99%
“…Aripiprazole, an atypical antipsychotic agent that acts as a partial agonist at dopamine D 2 receptors, has been proven to be effective and well-tolerated 9,10 . Several studies have shown that aripiprazole once monthly 400 mg (AOM400) effectively reduced hospitalization time and improved patient functionality 11–13 . Its safety profile was assessed in clinical trials that showed good tolerability and a low incidence of AEs 14 .…”
mentioning
confidence: 99%